Stomatal Conductance and Morphology of Arbuscular Mycorrhizal Wheat Plants Response to Elevated CO2 and NaCl Stress - Zhu, Xiancan; Cao, Qingjun; Sun, Luying; Yang, Xiaoqin; Yang, Wenying; Zhang, Hua (Frontiers in Plant Science, 2018)
Stomata play a critical role in the regulation of gas exchange between the interior of the leaf and the exterior environment and are affected by environmental and endogenous stimuli. This study aimed to evaluate the effect of the arbuscular mycorrhizal (AM) fungus, Rhizophagus irregularis, on the stomatal behavior of wheat (Triticum aestivum L.) plants under combination with elevated CO2 and NaCl stress. Wheat seedlings were exposed to ambient (400 ppm) or elevated (700 ppm) CO2 concentrations and 0, 1, and 2 g kg-1 dry soil NaCl treatments for 10 weeks. AM symbiosis increased the leaf area and stomatal density (SD) of the abaxial surface. Stomatal size and the aperture of adaxial and abaxial leaf surfaces were higher in the AM than non-AM plants under elevated CO2 and salinity stress. AM plants showed higher stomatal conductance (gs) and maximum rate of gs to water vapor (gsmax) compared with non-AM plants. Moreover, leaf water potential (Ψ) was increased and carbon isotope discrimination (Δ13C) was decreased by AM colonization, and both were significantly associated with stomatal conductance. The results suggest that AM symbiosis alters stomatal morphology by changing SD and the size of the guard cells and stomatal pores, thereby improving the stomatal conductance and water relations of wheat leaves under combined elevated CO2 and salinity stress.